Inflation Expectations and the Supply Chain - Albagli, Elias; Grigoli, Francesco; Luttini, Emiliano (Washington, D.C. : International Monetary Fund, 2022)
We show that firms rely on price changes observed along their supply chain to form expectations about aggregate inflation, and that these expectations have a complete pass-through to sales prices. Leveraging a unique dataset on Chilean firms merging expectation surveys and records from the VAT and customs registries, we document that changes in prices at which firms purchase inputs inform their forecasts of the economy's inflation. This is the case even if changes in input costs do not determine the inflation outcome. These findings reject the full-information rational-expectations hypothesis and are consistent with firms' disagreement about future inflation and inattention to macroeconomic news, which we document for Chile. Our results from a firm-level Phillips' curve estimation suggest that firms' beliefs about inflation are a key determinant for their price-setting decisions. Therefore, we argue that the channel we highlight in this paper has the potential to lead to dispersion in inflation expectations, price dispersion, and weaken the expectation channel of policies.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Deflation; Inflation; Price Level; Prices, Business Fluctuations, and Cycles